A Novel Approach to Enhance Bone Regeneration by Controlling the Polarity of GaN/AlGaN Heterostructures. (26th October 2020) - Zhang, Chenguang; Wang, Wenliang; Hao, Xiaodong; Peng, Yong; Zheng, Yulin; Liu, Jia; Kang, Yiyuan; Zhao, Fujian; Luo, Zhengtang; Guo, Junjie; Xu, Bingshe; Shao, Longquan; et al.
Abstract: Rapid and effective bone regeneration is still a major challenge in the clinical treatment of various bone diseases. Although recently developed electroactive materials have demonstrated high bone regeneration potential, the instability of the electrical stimulation and the unclear effects of the charge polarity on osteogenic differentiation hinder their clinical applications. In this work, GaN/AlGaN materials with well‐controlled polarity are used for the first time to induce endogenous electric stimulation and facilitate bone regeneration. By controlling the direction and magnitude of the piezoelectric and spontaneous polarization in the functional layer (GaN), charged GaN/AlGaN surfaces of opposite polarity, whose zeta potentials are within the range of the physiological potential, are obtained. Compared with N‐polarity GaN/AlGaN (with a positively charged surface), Ga‐polarity GaN/AlGaN (with a negatively charged surface) nanofilms show rapid and superior bone repair in vivo. In addition, the Ga‐polarity GaN/AlGaN hetero‐structures significantly promote the attachment, spreading, recruitment, and osteogenic differentiation of bone mesenchymal stem cells in vitro. Moreover, the bone morphogenetic protein‐6 (BMP6) expression profile in the early stages of osteogenic differentiation reveals that BMP6 may be an electrically sensitive osteogenic protein. This work sheds light on the application of III‐nitride materials in bone regeneration. Abstract : Endogenous electrical stimulation for enhancing bone regeneration is induced by well‐controlled polarity of GaN/AlGaN films. In this study, compared with N‐polarity GaN/AlGaN (with a positively charged surface), the Ga‐polarity GaN/AlGaN (with a negatively charged surface) provides the optimal electrical stimulation for the attachment, spreading, recruitment, and osteogenic differentiation of bone mesenchymal stem cells and thereby enhancing bone regeneration.